2005
DOI: 10.1016/j.cmet.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Foxa2 integrates the transcriptional response of the hepatocyte to fasting

Abstract: Survival during prolonged food deprivation depends on the activation of hepatic gluconeogenesis. Inappropriate regulation of this process is a hallmark of diabetes and other metabolic diseases. Activation of the genes encoding gluconeogenic enzymes is mediated by hormone-responsive transcription factors such as the cyclic AMP response element binding protein (CREB) and the glucocorticoid receptor (GR). Here we show using cell-type-specific gene ablation that the winged helix transcription factor Foxa2 is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
166
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(175 citation statements)
references
References 30 publications
7
166
0
2
Order By: Relevance
“…Indirect immunofluorescence and immunohistochemistry were performed as described previously (Zhang, Rubins, Ahima, Greenbaum & Kaestner, 2005). Slides subject to immunohistochemistry were counterstained with hematoxylin and eosin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect immunofluorescence and immunohistochemistry were performed as described previously (Zhang, Rubins, Ahima, Greenbaum & Kaestner, 2005). Slides subject to immunohistochemistry were counterstained with hematoxylin and eosin.…”
Section: Methodsmentioning
confidence: 99%
“…Liver RNA was isolated from young and old wild‐type mice, and quantitative reverse transcription–PCR was performed as described (Zhang et al., 2005). Protein extracts preparation and protein immunoblot analysis were performed as reported previously (Bochkis et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Post-developmentally, there are many examples of where prior binding by FoxA factors enables the subsequent binding by hormone receptors and other DNA-binding proteins (Gao et al 2003;Carroll et al 2005;Zhang et al 2005;Li et al 2009Li et al , 2012bPihlajamaa et al 2014), as previously covered in greater detail (Zaret and Carroll 2011). The mammalian circadian clock is driven by the CLOCK and BMAL1 transcription factors that rhythmically bind to nucleosomal target sites, promote incorporation of the histone variant H2A.Z, and enable the subsequent binding of other transcription factors (Menet et al 2014).…”
Section: Pioneer Factors In Cell Programming During Developmentmentioning
confidence: 99%
“…3A-B. The HNF6 expression plasmids was used to synthesize 35 S-methionine-labeled HNF6 proteins via in vitro transcription and translation (Fig. 3B, right panel), which were then used for binding reactions with various GST-C/EBP␣ fusion proteins (Fig.…”
Section: Hnf6 Transcriptional Synergy Requires the C/ebp␣ Ad1/ad2 Seqmentioning
confidence: 99%
“…Furthermore, Western blot analysis demonstrated that the CBP coactivator protein Diagram of HNF6 expression plasmids containing either the full-length HNF6 protein (WT), or N-terminal HNF6 protein that deleted either the homeodomain (⌬Homeo) or the cut-homeodomain (⌬Cut-Homeo) from the C-terminus, the cut-homeodomain alone (Cut-Homeo), or the cut domain alone (Cut). These HNF6 deletion plasmids were used to synthesize radioactively labeled HNF6 proteins using in vitro transcription and translation with 35 S-methionine, which were used in the in vitro GST-C/EBP␣ pull-down assays. The right panel shows the expression of these 35 S-labeled HNF6 deletion proteins as visualized via autoradiography following SDS-PAGE.…”
Section: Hnf6 Transcriptional Synergy Requires the C/ebp␣ Ad1/ad2 Seqmentioning
confidence: 99%